2019
DOI: 10.1136/bmjopen-2019-029199
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to recommended physical activity in lower-limb osteoarthritis: protocol for a qualitative study exploring patients and physiotherapist perspectives using the theoretical domains framework and behaviour change taxonomy

Abstract: IntroductionOsteoarthritis (OA) is the leading cause of disability and pain in older adults. Although increasing physical activity (PA) can help reduce symptoms, patients with lower-limb OA are less active than the general public. Although physiotherapists commonly deliver PA programmes, they lack knowledge of key barriers and facilitators to adherence to prescribed PA that patients with lower-limb OA experience while attending physiotherapy appointments (treatment period) and after discharge (post-treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Duong et al emphasise that the implementation of BCT’s, such as booster sessions should be used to improve exercise adherence, which supports the findings of this study [ 31 ]. The study by Willett et al concluded that peoples’ perceived beliefs about their capabilities should be targeted by facilitating psychosocial support and access to resources for PA maintenance post-discharge [ 36 ]. Therefore, the focus of the suggested monthly post-GLA:D GE groups should not only be on GE performance, individual adaptation and regular testing, but also on psychosocial support.…”
Section: Discussionmentioning
confidence: 99%
“…Duong et al emphasise that the implementation of BCT’s, such as booster sessions should be used to improve exercise adherence, which supports the findings of this study [ 31 ]. The study by Willett et al concluded that peoples’ perceived beliefs about their capabilities should be targeted by facilitating psychosocial support and access to resources for PA maintenance post-discharge [ 36 ]. Therefore, the focus of the suggested monthly post-GLA:D GE groups should not only be on GE performance, individual adaptation and regular testing, but also on psychosocial support.…”
Section: Discussionmentioning
confidence: 99%
“…First, conducted as a pragmatic, multicentre RCT, SmArt-E is more powerful and less prone to several biases (e.g., local effect bias, selection and performance bias, or concomitant therapy bias) compared to single-centre studies. Second, we evaluate an evidence-based exercise intervention [ 32 ], incorporating the NEMEX programme [ 38 ] and effective behaviour change techniques [ 103 ]. Third, given an overall 12-month intervention period, the implementation of refresher sessions after 6 months shall increase programme adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The in-depth perspectives of patients with lower-limb OA and their individual experiences of attending physiotherapy for the management of their OA related symptoms were sought to propose a theoretically informed intervention [ 40 ]. This study utilised a phenomenological framework [ 41 ], which followed a published protocol [ 42 ], and was reported using the COnsolidated criteria for REporting Qualitative research (COREQ) [ 43 ]. A summary of the study processes is outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%